Responsibility of Hotels in Tornio - Timonen, Katariina (2024)
This thesis project aims to analyze the current state of responsibility and responsibility certificates acquired in the hotels of Tornio. Examining the current level of responsibility and responsible operations is vital to be capable of developing responsibility further in the Tornio area. Additionally, the study includes an examination of the hotels in Rovaniemi to get comparable information on the sustainability and responsible activities in the city hotels in Lapland. The thesis was commissioned by Business Tornio, a company that aids local entrepreneurs in starting a company and aims to help local companies in Tornio grow and become globally known. Qualitative research methods were utilized to achieve the goals of the study. The method of interviewing was applied to research the level of responsibility of hotels in Tornio. The representatives of the hotels answered to theme interview questions to provide information on their level of responsibility and responsible operations. The method of content analysis was applied to examine hotels in Rovaniemi. The content analysis examined the responsible practices of hotels in Rovaniemi by examining their web pages and Instagram content. The findings revealed that despite Tornio’s hotels having responsible practices and business operations, the companies had not acquired any responsibility certificates. The examination of hotels in Rovaniemi provided information on how the hotels of Tornio can enhance their level of responsibility. Additionally, the examination of hotels in Rovaniemi provided information on what kind of certificates hotels in Tornio could acquire. The study is useful for local accommodation companies in Tornio and other similar accommodation companies who want to develop their level of responsibility. Companies participating in the study can utilize this thesis to analyze the responsibility operations in Tornio and to learn which practices they could apply to their businesses.